2004
DOI: 10.1136/jcp.2004.016055
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metastasis from a bronchial carcinoid: report of a case presenting with diffuse thickening of the left ventricular wall

Abstract: Bronchial carcinoids are low grade malignancies with an excellent prognosis and a low incidence of metastases. This report describes a case of a typical carcinoid tumour with metastases to the spine after four years and to the heart after eight years. Carcinoid tumours rarely metastasise to the heart and previous reports have identified gastrointestinal primaries as the source in most cases. This is the first published case of typical carcinoid tumour that metastasised to the heart from a bronchial primary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Even if patients do not complain of any symptoms, patients with carcinoid tumors should be followed up carefully using effective inspection methods. We reviewed 50 cases that described skeletal metastasis from carcinoid tumors (3,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The characteristics of the reported patients are shown in Table Ⅰ.…”
Section: Discussionmentioning
confidence: 99%
“…Even if patients do not complain of any symptoms, patients with carcinoid tumors should be followed up carefully using effective inspection methods. We reviewed 50 cases that described skeletal metastasis from carcinoid tumors (3,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The characteristics of the reported patients are shown in Table Ⅰ.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current experience of 36 published case reports in the literature, it is apparent that the majority of cardiac metastases originate from NET of the gastrointestinal tract [21] . Other sites of the primary tumor include the pancreas [23] and bronchopulmonary system [24,25] , but in individual patients the location of the primary tumor is unknown [26] . The occurrence of myocardial metastases has been described more often in patients with functioning tumors than in those with nonfunctioning tumors, although the significance of this observation is unclear.…”
Section: Cardiac Metastasesmentioning
confidence: 99%
“…Cardiac metastases rarely display clinical symptoms ( ! 30%) but when present include dyspnea, arrhythmias or accentuation of the carcinoid syndrome [22,24,[34][35][36][37][38] .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…33 Varied clinical presentations include constrictive pericarditis, 34 complete heart block, 35 ST-segment elevation myocardial infarction due to coronary spasm, 36 and restrictive cardiomyopathy. 37 A clinical presentation with cyanosis and hypoxia secondary to a combination of right-sided heart disease and an interatrial shunt due to the presence of patent foramen ovale (PFO) has also been reported. 38,39 An interesting clinical finding may be dermatitis of sun-exposed areas, due to pellagra resulting from niacin deficiency, as up to 60% of tryptophan is used in serotonin synthesis by the tumor.…”
Section: Clinical Featuresmentioning
confidence: 96%